2022
DOI: 10.1128/msystems.00100-22
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium lactis Probio-M8 Adjuvant Treatment Confers Added Benefits to Patients with Coronary Artery Disease via Target Modulation of the Gut-Heart/-Brain Axes

Abstract: Despite recent advances in therapeutic strategies and drug treatments (e.g., statins) for coronary artery disease (CAD), CAD-related mortality and morbidity remain high. Active bidirectional interactions between the gut microbiota and the heart implicate that probiotic application could be a novel therapeutic strategy for CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…Although these microbes are part of the normal gut microbiota, they might act as opportunistic pathogens under suboptimal conditions. Oscillibacter -like organisms are thought to be associated with high-fat-diet-induced gut dysfunction, possibly via disrupting the gut barrier integrity in the proximal colon [ 53 ]; Hungatella hathewayi has been found to advance intestinal tumorigenesis via regulating multiple tumor suppressor gene promoters on the epigenetic level [ 54 ]; Eubacterium rectale could initiate colorectal cancer through promoting colon inflammation [ 55 ]. Therefore, one possible mechanism of the tumor suppressor effect of Probio-M9 is inhibiting certain opportunistic microbes in the gut environment in mammary tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although these microbes are part of the normal gut microbiota, they might act as opportunistic pathogens under suboptimal conditions. Oscillibacter -like organisms are thought to be associated with high-fat-diet-induced gut dysfunction, possibly via disrupting the gut barrier integrity in the proximal colon [ 53 ]; Hungatella hathewayi has been found to advance intestinal tumorigenesis via regulating multiple tumor suppressor gene promoters on the epigenetic level [ 54 ]; Eubacterium rectale could initiate colorectal cancer through promoting colon inflammation [ 55 ]. Therefore, one possible mechanism of the tumor suppressor effect of Probio-M9 is inhibiting certain opportunistic microbes in the gut environment in mammary tumor-bearing mice.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics are "live microorganisms which when administered in adequate amounts confer a health benefit on the host" 1 . Moreover, probiotics have been increasingly used in clinical settings in adjunct to conventional drugs for disease management [2][3][4][5][6][7] . However, there are potential safety concerns of probiotic use in patients with severe disease 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Bifidobacteria also yield probiotic strains with potential benefit in atherosclerosis. Patients with CAD were enrolled in a randomized, double-blind, placebo-controlled trial examining the efficacy of the probiotic strain Bifidobacterium lactis Probio-M8 in combination with conventional treatment involving lipid-lowering (atorvastatin) and β-blockade (metoprolol) [ 45 ]. Based on the study results, the study group reported significant improvement in anginal, anxiety, and depressive symptoms assessed through the Seattle Angina Questionnaire, Self-Rating Anxiety Scale, and the Self-Rating Depression Scale, respectively, compared to the control group.…”
Section: Current Therapeutic Interventionsmentioning
confidence: 99%